OPTIMIZING ETL IMPLEMENTATION THROUGH REUSABLE TEMPLATES AND VALIDATION FRAMEWORKS - Devika Rajhamundry (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores strategies for optimizing ETL implementation by developing reusable templates and robust data validation frameworks. It examines the evolving landscape of Business Intelligence and data management, addressing key challenges organizations face in ETL development, implementation, and maintenance. The article presents comprehensive solutions through standardized templates, parameterization approaches, and database validation frameworks. The article investigates development standards, quality assurance practices, and their impact on operational efficiency. By analyzing implementation methodologies across various organizations, the article demonstrates how structured approaches to ETL development can significantly reduce costs, improve data quality, enhance team productivity, and accelerate deployment cycles while maintaining system reliability and performance.